Pengaruh Employee Engagement Terhadap Organizational Citizenship Behavior (OCB) Pegawai Di Rutan Kelas IIB Humbang Hasundutan - Lidya Seventina Ompusunggu; Denny Nazaria Rifani (Widya Manajemen, 2023)
One of the factors that make employee organizational citizenship behavior exist in carrying out duties and responsibilities in the organization is employee engagement. It is necessary for every employee to have an employee to encourage OCB attitudes. This study aims to determine employee engagement's effect on the organizational citizenship behavior of employees in Rutan Class IIB Humbang Hasundutan. The research method is a descriptive quantitative research method consisting of six data analysis techniques using IBM 26 SPSS. In the results of the significance test, the calculated value > t-tabel (7.759 > 0.266) with a ratio of the significance of 0.000 < 0.05. This indicates that H0 is rejected and Ha is accepted which means that there is a significant influence of the employee engagement variable on the organizational citizenship behavior of employees in the Class IIB Detention Center Humbang Hasundutan.